Penerapan Media Audio Visual dalam Meningkatkan Hasil Belajar Mata Pelajaran PAI Menghafal Bacaan Shalat Kelas IV UPT SDN 12 Lunang - Mustika, Inda (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve the learning outcomes of fourth-grade students in Islamic Religious Education using audio-visual media. The research was conducted in two cycles, involving planning, implementation, observation, and reflection stages. The results indicate an improvement in students’ learning outcomes from cycle I to cycle II. The average score increased from 63.25 in cycle I to 72.75 in cycle II, while the percentage of students achieving mastery rose from 25% to 45%. However, some challenges were identified, such as students’ lack of understanding of the teaching methods and low active participation. Reflections from cycle II highlight the importance of time management, adaptive teaching strategies, and enhancing student motivation for more effective learning. This study demonstrates that the use of audio-visual media can be an effective method for improving students’ learning outcomes, especially when accompanied by better planning and implementation.